In Vitro Stability of the Biological Activity of Voriconazole against Acanthamoeba castellanii - Barbara Czerniak Rodrigues; Maria Luiza Carneiro Büchele; Carolina de Jesus de Camargo; Fabíola Branco Filippin-Monteiro; Karin Silva Caumo (Parasitologia, 2023)
Acanthamoeba keratitis (AK) is a rare cornea disease caused by species of the Acanthamoeba genus. The antifungal voriconazole blocks the ergosterol synthesis in the protozoan membrane and is active against the cysts and trophozoites of Acanthamoeba spp. Due to the low stability of voriconazole, its options for eye drops are scarce. This study aimed to investigate the stability of the biological activity of voriconazole against two strains of Acanthamoeba castellanii and one clinical isolate from a patient with AK. To evaluate the stability of the biological activity of voriconazole, strains of A. castellanii (ATCC 50492) were exposed to different periods and voriconazole concentrations stored at 4 °C for 7, 15, and 30 days. The cytotoxicity assays were performed using SIRC (ATCC CCL-60™) cell line. The results indicated the amoebicidal effect of voriconazole against Acanthamoeba spp. within 24 h and 48 h of exposure, and the voriconazole solution was stable and retained antiamoebic activity when stored at 4 °C for up to 30 days. In the cytotoxicity test, the result demonstrated low cytotoxicity of the drug to the corneal rabbit cell line. However, there is a need to carry out further synergistic effects with other antiamoebic drugs and then in vivo experiments in the AK animal model.